Assessment of German Speaking Skills Niveau A2 Based on Case Method - Surya Masniari Hutagalung; Tanti Kurnia Sari (Budapest International Research and Critics University, 2022)
This research is part of a development research entitled Development of Hybrid Learning Tools for Sprechen A2 Courses Based on Case Method and Team Based Project. This article contains the process of developing the assessment instruments carried out in the study, and the results of instrument analysis carried out by German language learning experts. This part of the study aims to produce a assessment of German A2 speaking skills based on case study. The development model adopted is the Thiagarajan 4D development model with stages (1) define, (2) design, (3) develop, and (4) disseminate. The stage that is carried out only until the third stage is develop, because it must first be combined with the material, so that it can then be published and disseminated. The development process resulted in a set of case method-based test instruments, totaling eight themes, one case each. Each instrument is equipped with an assessment rubric by adapting the assessment rubric of international standards. The research instrument was declared feasible for use in Sprechen A2 learning according to the validation results which showed an average score of 92 for all components of the question.